TRANSFORMATION OF MOTORICAL ABILITIES CHILDREN STRATURE FROM 10 TO 12 YEARS - Branimir Mikić; Biljana Mikić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
because of solving some specifical tasks which areappeared in all phases of game. Player must be able, that on max. level distinguish his motorical abilities (speed, explosive power, coordination...).If we want quality respond to request of game, the player must be motoricaly build up and condicionaly ready, that we can achieve with one sistematical way of planning and programming of training process. Conditional preparation of young groups need to be very good structured process of evolved and maintenance conditional abilities with contents, methods, and strain which will stimulate dynamic progress football players , with all development of sensibile phases for progrsss comditional abilities( Bompa,T.,2005). In this exoloration, it was target to establish how much and how application trenage technology affect on progess of motorical abilities football players (children) strature from 10 to 12 years, which training small football.For analise and processing informations applicate is :T-test with target to establish quantitative changes in motorical space , like as factory analise with target to establish qualitative changes in structure of motorical space of explorated pattern with influence of training technology characteristical for small football.